Mechanical versus biological aortic valve implants in the elderly. A comparison of early and mid-term results - Thulin,Lars I. (2001)
OBJECTIVE: Our aim was to compare, in a non randomized study, the surgical outcome in elderly patients with mechanical (Group 1; n=83) and bioprosthetic valve implants (Group 2; n=136). METHODS: During a three year period, 219 patients >75 years underwent Aortic Valve Replacement. The groups matched according to age, sex, comorbidity, valve pathology and concomitant Coronary Artery Bypass Surgery. Follow-up was a total of 469 patient-years (mean follow-up 2.1 years, maximum 4,4 years). RESULTS: Operative mortality was zero and the overall early mortality was 2.3 % (within 30 days). Actuarial survival was 87.5 ± 4.0% and 66.1 ± 7.7% (NS) at 4 years in Group 1 and Group 2, respectively. Freedom from valve-related death was 88.9 ± 3.8% in Group 1 and 69.9±7.9% (NS) in Group 2 at 4 years. CONCLUSION: Aortic Valve Replacement in the elderly (>75 years) is a safe procedure even in cases where concomitant coronary artery revascularization is performed. Only a few anticoagulant-related complications were reported and this may indicate that selected groups of elderly patients with significant life expectancy may benefit from mechanical implants .